Micropore Structure and Fractal Characteristics of Clays Due to Freeze-Thaw and Compression Based on Mercury Intrusion Porosimetry - Wang, Shengfu; Lv, Liang; Xue, Kaixi; Zhang, Dongjie; Li, Mingdong; Li, Dongwei; Yuan, Chang (Frontiers in Earth Science, 2022)
The artificial ground freezing method has been widely used in shield end reinforcement and connecting channel reinforcement of urban subway tunnel in water rich soft soil area. Accurate quantification of micropore change and redistribution due to freeze-thaw is important for understanding frost heave and thaw settlement of soft soils including mucky clay and silty clay. This paper presents Mercury Intrusion Porosimetry (MIP) date for mucky clay and silty clay specimens before and after freeze-thaw and compression. MIP tests were conducted on the soil samples of undisturbed soil, frozen-thawed soil, compressed soil and compressed frozen-thawed soil. The micro pore size division method for mucky clay and silty clay was proposed. The micro pore changes of clays in different states were analyzed by fractal theory. The micro pore distribution characteristics of mucky clay and silty clay were studied, and the pore volume distribution and pore surface area distribution were calculated by capacity dimension. The particle contact and pore change before and after freeze-thaw and compression were analyzed quantitatively. The results show that, freeze-thaw and compression had different effects on pore characteristics of clays, the pore volume of mucky clay and silty clay were mainly distributed in micropores and ultramicropores, accounting for more than 80% of the total volume. Both the pore volume distribution and the pore surface area distribution with fractal characteristics.